T‐cell STAT3 is required for the maintenance of humoral immunity to LCMV. Issue 2 (15th December 2014) - McIlwain, David R.; Grusdat, Melanie; Pozdeev, Vitaly I.; Xu, Haifeng C.; Shinde, Prashant; Reardon, Colin; Hao, Zhenyue; Beyer, Marc; Bergthaler, Andreas; Häussinger, Dieter; Nolan, Garry P.; Lang, Karl S.; et al.
<x xml:space="preserve">Abstract</x> STAT3 is a critical transcription factor activated downstream of cytokine signaling and is integral for the function of multiple immune cell types. Human mutations in STAT3 cause primary immunodeficiency resulting in impaired control of a variety of infections, including reactivation of latent viruses. In this study, we investigate how T‐cell functions of STAT3 contribute to responses to viral infection by inducing chronic lymphocytic choriomeningitis virus (LCMV) infection in mice lacking STAT3 specifically in T cells. Although mice with conditional disruption of STAT3 in T cells were able to mount early responses to viral infection similar to control animals, including expansion of effector T cells, we found generation of T‐follicular helper (Tfh) cells to be impaired. As a result, STAT3 T cell deficient mice produced attenuated germinal center reactions, and did not accumulate bone marrow virus specific IgG‐secreting cells, resulting in failure to maintain levels of virus‐specific IgG or mount neutralizing responses to LCMV in the serum. These effects were associated with reduced control of viral replication and prolonged infection. Our results demonstrate the importance of STAT3 in T cells for the generation of functional long‐term humoral immunity to viral infections.